2001
DOI: 10.1046/j.1442-2042.2001.00291.x
|View full text |Cite
|
Sign up to set email alerts
|

Schinzel–Giedion syndrome

Abstract: A 2-month-old girl was brought to the Department of Pediatrics at Wakayama Rosai Hospital because of poor feeding since 1 month of age. She was the third child of young healthy nonconsanguineous parents whose first son was healthy but whose second son had died of 18 trisomy. Physical examination showed midfacial hypoplasia with coarse dysmorphic features, choanal stenosis, remarkable abdominal distention and bilateral talipes equivarus. Abdominal ultrasonography, computed tomography and drip infusion pyelogram… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
14
0

Year Published

2008
2008
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(14 citation statements)
references
References 10 publications
0
14
0
Order By: Relevance
“…Typically, SGS patients have large fontanelles (n = 37/41), a prominent forehead (n = 41/44), bitemporal narrowing (n = 32/36), shallow orbits or prominent eyes (n = 36/38), hypertelorism (n = 36/42) a retracted and shortened midface (n = 45/45) and full cheeks, leading to a facial frontal silhouette in the shape of a number eight [19]. Additionally, most patients have a deep groove under the eyes (n = 38/39), upslanting palpebral fissures (n = 21/26) and a short nose with a bulbous nasal tip (n = 43/44).…”
Section: Resultsmentioning
confidence: 99%
“…Typically, SGS patients have large fontanelles (n = 37/41), a prominent forehead (n = 41/44), bitemporal narrowing (n = 32/36), shallow orbits or prominent eyes (n = 36/38), hypertelorism (n = 36/42) a retracted and shortened midface (n = 45/45) and full cheeks, leading to a facial frontal silhouette in the shape of a number eight [19]. Additionally, most patients have a deep groove under the eyes (n = 38/39), upslanting palpebral fissures (n = 21/26) and a short nose with a bulbous nasal tip (n = 43/44).…”
Section: Resultsmentioning
confidence: 99%
“…Prior to delivery, polyhydramnios was noted with Patient 1. Among nine SGS patients for whom prenatal findings were reported, polyhydramnios was observed in two and fetal hydronephrosis in six . Polyhydramnios is caused by excess production of amniotic fluid or poor swallowing of amniotic fluid by the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Prenatal ultrasonography thus predicted hydronephrosis in six of the nine fetuses for which findings have been reported. Touge et al reported that many SGS patients displayed several types of urinary tract anomalies, such as pyeloureteral junction stenosis, ureterovesical junction stenosis, and vesicoureteral reflux. These anomalies caused hydronephrosis with or without hydroureter.…”
Section: Discussionmentioning
confidence: 99%
“…Only 36 cases have been reported to date [37][38][39]. Common features include normal intrauterine growth and gestation with severe intellectual disability and low physical growth after birth, coarse facial appearance with midfacial hypoplasia, abnormal auricles and deep groves under eyes.…”
Section: Vesicoureteral Refluxmentioning
confidence: 96%
“…Common features include normal intrauterine growth and gestation with severe intellectual disability and low physical growth after birth, coarse facial appearance with midfacial hypoplasia, abnormal auricles and deep groves under eyes. Epilepsy, spasms, hydronephrosis and genital anomalies are also frequent findings [38]. About half of patients die before 2 years of age due to respiratory failure, epilepsy and infection.…”
Section: Vesicoureteral Refluxmentioning
confidence: 99%